Cover Picture: Discovery of NVP‐LEQ506, a Second‐Generation Inhibitor of Smoothened (ChemMedChem 8/2013). Issue 8 (29th July 2013) - Peukert, Stefan; He, Feng; Dai, Miao; Zhang, Rui; Sun, Yingchuan; Miller‐Moslin, Karen; McEwan, Michael; Lagu, Bharat; Wang, Kate; Yusuff, Naeem; Bourret, Aaron; Ramamurthy, Arun; et al.
<x xml:space="preserve">Abstract</x> The front cover picture shows the structure of NVP‐LEQ506, a new and potent inhibitor of the transmembrane receptor Smoothened. This compound, currently in clinical trials, binds to Smoothened, resulting in inhibition of the Hedgehog signaling pathway and thus preventing cell proliferation mediated by Gli transcription factors. The identification of this low‐nanomolar inhibitor was achieved through systematic structure–property relationship studies in which potency, solubility, and off‐target effects were optimized. This discovery opens new treatment options for patients with cancers driven by Hedgehog pathway mutations such as medulloblastoma, a malignant brain tumor. For more details, see the Communication by Stefan Peukert et al. on p. 1261 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>